1981
DOI: 10.1080/05698198108983040
|View full text |Cite
|
Sign up to set email alerts
|

Some Effects of Amines on Zinc Dialkyldithiophosphate Antiwear Performance as Measured in 4-Ball Wear Tests

Abstract: A&~cr.se itrtercrctiots 1.f zinc dialk~lditl~iopl~ospIrnle (ZDPs) wi/h ollrer rcclirired rrddi~iues it2 crtz engine oil 1s otle f(rc/or cof~lributing lo //LC I~iglr phosp1~orrr.s cotrtenl of sottre e7tgine oils. Si?~ccphos/)hortrs poisolrs eslrrirr.sl gcrs e~trission c~/alysts, rucrys lo redztce the nclvcne irrtercrctiotr.~ crre 6eiti.g sclzrgl~l. The ZDP-amitre i,tz/erc~ctio?~ wtrs i?tvestigctled cis a ttroclel uf sztcl~ ntz interclctiotr. Above n criticnl coi~cer~frcrliot~. (11t11~ties c(rti C ( I I L C C~ /… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…A lot of investigations have been conducted to evaluate the performances of additive mixtures and to determine the composition of associated tribofilms. Several factors were identified as playing a role: additive structure [1,2], additives concentration [3][4][5][6], base oil nature [7,8], …, or combinations of these parameters. A detailed review on published information on that topic was written by Willermet [9].…”
Section: Introductionmentioning
confidence: 99%
“…A lot of investigations have been conducted to evaluate the performances of additive mixtures and to determine the composition of associated tribofilms. Several factors were identified as playing a role: additive structure [1,2], additives concentration [3][4][5][6], base oil nature [7,8], …, or combinations of these parameters. A detailed review on published information on that topic was written by Willermet [9].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that primary fatty amine restricts the low shear strength MoS 2 sheets forming on the surface. Rounds [40] investigated the effect of organic friction modifiers, zinc dialkyldithiophosphate anti-wear, metallic detergent and succinimide dispersant on frictional performance in a 4-ball friction tester at different loads and at the temperature of 93℃ for a 52100 steel surface. It was observed that a higher quantity (e.g.…”
Section: Ofmmentioning
confidence: 99%
“…These studies examined the synergistic and antagonistic behaviors in various tribological properties in combinations of surface reactive additives [10,15,16]. Narayan [17] reported that a combination of nanoparticle and microparticle treatments for engines enhances fuel efficiency and engine life, and reduces exhaust emissions; the nanoparticles used in this study were chosen from a class of hard materials (alumina, silica, ceria, titania, diamond, cubic boron nitride, and molybdenum oxide), whereas the microparticles were chosen from a class of layer-structured materials (graphite, hexagonal boron nitride, magnesium silicates, and molybdenum disulfide).…”
Section: Introductionmentioning
confidence: 99%